Evaluation of bioactivity against some pathogenic bacteria and oxidation for fungal secondary metabolites of Fusarium solani isolated from soil - Rashid Rahim Hateet (مجلة بغداد للعلوم, 2017)
The study included isolate and diagnose fungus Fusarium solani of the local soil and purified and development in the PDB medium and the filtrate extracted using a solvent (Ethyl acetate) to obtain the fungal secondary metabolites extract. This extract has shown bioactivity against both reference isolates (E.coli (ATCC25922) and S.aureus(NCTC6571)) and pathogenic isolates S.pyogenes, K. pneumonia and S.typhimurium using agar disk diffusion technique , The diameters of the inhibition zones of fungal secondary metabolites24.0 mm against E.coli and 31.5 mm against S.aureus,and 34.0 mm against K.pneumoniae and 18.0 mm against S.pyogenes and 33.5mm against S.typhimurium. The test revealed the minimum inhibitory concentration (MIC) of the fungal extract less inhibitor concentration towards our isolation S.aureus was 6.25 µg/ ml also less deadly concentration (MBC).Also against isolate S.aureus was 12.5µg/ ml. also fungal extract showed no toxicity toward human red blood cells. Tested the antioxidant of the fungal extract by measuring its ability to be reduced iron duo ions (Fe Π) have shown high rates of inhibition. The metabolic product of soil fungi can be an alternative source of commercial anti-bacterial.